Mesto na prehodu - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Development trends of Slovene cities are similar to those in developed countries, which result in bigger and bigger functional and social heterogeneity. Certain processes in city centres, at continuously built-up city teritorry and outskirts, are represented on the examples of Ljubljana and Maribor. At the end, function of geography in relation to studying and searching for ways in respect of more harmonious development of cities is defined.
Keywords: mesta; prostorski razvoj; regionalni razvoj; Slovenia; Slovenija; suburbanizacija; urbana geografija; urbanizacija